2020
DOI: 10.1182/blood.2019002326
|View full text |Cite
|
Sign up to set email alerts
|

AML displays increased CTCF occupancy associated with aberrant gene expression and transcription factor binding

Abstract: CCTC-binding factor (CTCF) is a key regulator of gene expression through organization of the chromatin structure. Still, it is unclear how CTCF binding is perturbed in leukemia or in cancer in general. We studied CTCF binding by chromatin immunoprecipitation sequencing in cells from patients with acute myeloid leukemia (AML) and in normal bone marrow (NBM) in the context of gene expression, DNA methylation, and azacitidine exposure. CTCF binding was increased in AML compared with NBM. Aberrant CTCF binding was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 173 publications
(156 reference statements)
0
17
0
Order By: Relevance
“…We found that predisposed patients, when compared to nonfusion patients, had significantly more DNA breakage at a select group of TOP2‐sensitive, CTCF‐, RAD21‐, and SMC3‐binding sites. A recent study found that CTCF binding was increased in AML patients when compared to normal bone marrow cells, further implicating CTCF in AML pathogenesis 59 . More importantly, DNA breakage at these TOP2‐sensitive sites specifically increased in a dose‐dependent manner, and increased DNA breakage in etoposide‐treated samples was also associated with stronger protein binding at CTCF, RAD21, and SMC3 sites.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We found that predisposed patients, when compared to nonfusion patients, had significantly more DNA breakage at a select group of TOP2‐sensitive, CTCF‐, RAD21‐, and SMC3‐binding sites. A recent study found that CTCF binding was increased in AML patients when compared to normal bone marrow cells, further implicating CTCF in AML pathogenesis 59 . More importantly, DNA breakage at these TOP2‐sensitive sites specifically increased in a dose‐dependent manner, and increased DNA breakage in etoposide‐treated samples was also associated with stronger protein binding at CTCF, RAD21, and SMC3 sites.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study found that CTCF binding was increased in AML patients when compared to normal bone marrow cells, further implicating CTCF in AML pathogenesis. 59 More importantly, DNA breakage at these TOP2-sensitive sites specifically increased in a dose-dependent manner, and increased DNA breakage in etoposide-treated samples was also associated with stronger protein binding at CTCF, RAD21, and SMC3 sites. We are also intrigued by the difference in etoposide response among the 34 shared sites (by TOP2, CTCF, RAD21, and SMC3).…”
Section: Discussionmentioning
confidence: 93%
“…Evidences have shown that somatic gene mutations such as RUNX1 mutation affected transcription activation in AML. 18 In our study, we further identified the association between SNHG7/12 and common gene mutations such as IDH1/2, RUNX1 and NPM1 mutations in patients with AML. However, the potential connections between SNHG7/12 expression and these gene mutations remain poorly defined.…”
Section: Discussionmentioning
confidence: 63%
“…One question arising is how can we perturb chromatin interactions in cancer? Aza-cytidine, a drug commonly used in AML treatment, has recently been shown to alter CTCF levels (37). We speculate that these drugs may work in part by leading to alterations in chromatin interactions, such as the FIRE at MEIS1 , leading to downregulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%